Semen Analysis in Fertiliser Factory Workers - Sri Nita; Yulia Hariani; Arum Setiawan (Majalah Kedokteran Sriwijaya, 2019)
Study case-control has been conducted to analyse the relationship of occupational exposure in fertilizer plant with semen analysis. The case is the exposed and control group is unexposed. The number of samples for each group was 27. Data is analysed using chi-square and t-test. The result of the research has obtained the characteristic of the workers in the exposed group were the age of 20-30 years old, the working period of 3-5 years, 8 hours/day work, using personal protective equipment (PPE) and not smoking. The unexposed group have 20-30-year-old characteristics, 5-10 years of service, 8 hours/day work, no PPE and smoking. Macroscopic characteristics of semen liquefaction, viscosity, pH and colour of the two groups were no different. Semen volume under 1.5 ml of 18.5% (exposed) and 7.4% (unexposed) with p>0.05; OR=2.84. Microscopic characteristics of semen for motility and viability were not different in the two groups. Low spermatozoa number in exposure group was 55.6% and not exposed 18.5% with a p value<0.05 and OR 5.5. Normal spermatozoa morphology of exposed group workers was 28% and the group was not exposed to 34%. It could be concluded that there is a relationship between occupational exposure and semen analysis.